CCEA GCSE Mathematics Foundation Practice Book for 2nd Edition. - Linda Liggett; Robin Liggett (London, UNKNOWN : Hodder Education Group, 2017)
Provide structured support and extra practice with hundreds of practice questions that focus on problem-solving, building the exam skills needed to succeed in the new GCSE specifications. - Enhance learning and build exam skills with extra practice designed to support the student books - Help develop students' skills and prepare them effectively for their exam with questions that cover all units of the new syllabus - Build problem-solving and mathematical reasoning skills with a range of practice questions.
37 Parallel lines (M1)38 Time (M1); 39 Units of measurement (M1); 40 Scale drawings (M5); 41 Reading scales (M5); 42 Pythagoras' theorem (M2); 43 Bearings (M6); 44 Perimeter, area and volume 1 (M1); 45 Symmetry and transformations (M5, M6); 46 Circles (M1, M2); 47 Perimeter, area and volume 2 (M2); 48 Metric and imperial units (M5); 49 Constructions and loci (M5, M6); 50 Effect of enlargement on shapes (M6); 51 Compound measures (M1, M2); 52 Data and questionnaires (M1, M2); 53 Statistical averages and spread (M1, M2); 54 Statistical diagrams 1 (M1); 55 Statistical diagrams 2 (M1, M2).
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Mathematics -- Problems, exercises, etc; MATHEMATICS / Essays; MATHEMATICS / Pre-Calculus; MATHEMATICS / Reference; Electronic books